Heterogeneous catalysis at nanoscale for energy applications - Tao, Feng, 1971-; Schneider, William F., 1964-; Kamat, Prashant V. (2015)
"A key technology in the chemical and energy industries, heterogeneous catalysis is growing in importance owing to its potential for solving global energy problems. This volume covers both fundamental concepts and recent advances in the field, offering an in-depth look at the synthesis and characterization of nanocatalysts as well as a mechanistic understanding of catalysis at atomic level for important processes of energy conversion. Comprehensive and authoritative, the book provides scientists and engineers with a foundation for pioneering the next technical catalysts for energy efficient technologies"--
"Covers both fundamental concepts and recent advances in the field of heterogeneous catalysis, offering an in-depth look at the synthesis and characterization of nanocatalysts as well as a mechanistic understanding of catalysis at the atomic level for important processes of energy conversion"--
.
Includes bibliographical references and index.
Keywords: Heterogeneous catalysis; Energy conversion; Nanochemistry; SCIENCE / Chemistry / Physical & Theoretical